FRI0533 The Diagnostic Performance of Post-Contrast 3-D Ultrashort Echo Time Sequence of Sacroiliitis in Patients with Axial Spondyloarthropathy Comparing with Conventional Post-Contrast Fat Suppressed T1 Weighted Sequence. (15th July 2016) - Jung, K.H.; Kim, Y.J.; Park, W.; Lim, M.J.; Carl, M.; Kim, D.E.; Hwang, M.; Cha, J.G.; Kwon, S.
Abstract : Background: Axial spondyloarthropathies (axSpA) are chronic inflammatory diseases affecting the sacroiliac joint, spine, peripheral joint, and entheses. Entheses are emphasized as one of the primary targets of axSpA, but they show little signal on conventional clinical magnetic resonance (MR). Recently, the ultrashort echo time (UTE) sequence has been reported to be useful in detecting a signal from the tissues with short T2 such as the ligaments, periosteum, and cortical bone. Contrast enhancement study of UTE sequence showed increased enhancement as a consequence of angiogenesis in a diseased tendon and fibrocartilage. To our knowledge, no prior study has compared the diagnostic performances of post-contrast 3D UTE and conventional post-contrast fat suppressed T1 weighted sequence (FST1WI) for sacroiliitis in patients with axSpA. Objectives: To compare the diagnostic performance of post-contrast 3D UTE and conventional FS1WI for sacroiliitis. Methods: Total 16 patients with axSpA (asSpA group: 10 men, 6 women, mean age: 35.56 years [range: 24–52 years], human leukocyte antigen B 27 positivity 81.25%, ) and 10 patients with mechanical back pain (control group: 2 men, 8 women, mean age: 58.6 years [range 34–74 years]) were enrolled in this prospective study. All patients underwent oblique coronal short tau inversion recovery sequence (STIR), pre/post contrast fat suppressed (FS) 3D UTE, and post contrast FST1WI. Active inflammation of the sacroiliac joint was quantitatively analyzed and scored on post-contrast FS 3D UTE and post contrast FST1WI for inflammatory findings, such as osteitis, synovitis, capsulitis, and enthesitis, by two musculoskeletal radiologists with a consensus. The score per active inflammatory finding of 3D UTE and post contrast FST1WI was compared between axSpA group and control group using Wilcoxon rank test. Results: The axSpA group showed higher scores for osteitis and synovitis on both post-contrast FS 3D UTE ( P =0.018, 0.025, respectively) and post-contrast FST1WI ( P =0.003, 0.005, respectively) and for enthesitis on post-contrast FS 3D UTE with a statistical significance ( P =0.004). Post-contrast FS 3D UTE showed statistically significant lower scores for all inflammatory findings than enhanced FS T1 WI sequences did ( P <0.05). Conclusions: Post contrast 3D UTE can differentiate axSpA and mechanical back pain, especially when considering enthesitis. Although it showed slightly lower diagnostic performance for the active inflammatory finding than post contrast FST1WI did, post contrast 3D UTE might play a supplementary diagnostic role for early diagnosis of axSpA. Disclosure of Interest: K. H. Jung: None declared, Y. J. Kim: None declared, W. Park: None declared, M. J. Lim: None declared, M. Carl Employee of: GE Healthcare, D. E. Kim Employee of: GE healthcare, M. Hwang Employee of: GE Healthcare, J. G. Cha: None declared, S. Kwon: None declared